The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1038/sj.bjc.6600715
|View full text |Cite
|
Sign up to set email alerts
|

Percentage of the positive area of bone metastasis is an independent predictor of disease death in advanced prostate cancer

Abstract: We addressed in this study whether quantifying the extent of disease on bone scans can predict the disease death of patients with advanced prostate cancer using computer-assisted image analysis. Pretreatment radionuclide bone scans were reviewed in 56 patients with bone metastases from prostate cancer, and the percentage of the positive area on a bone scan (%PABS) was quantified automatically using a personal computer with the NIH Image program for estimation of the accurate extent of metastatic bone lesions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(57 citation statements)
references
References 14 publications
1
55
0
1
Order By: Relevance
“…Rigaud et al [19] showed in a series of 86 patients with prostate cancer metastases that metastases involving the axial skeleton carry a better prognosis than lesions in appendicular sites. It has also been demonstrated that percentage of positive area for metastases on a bone scan independently predicts survival in metastatic prostate cancer [20] .…”
Section: Discussionmentioning
confidence: 99%
“…Rigaud et al [19] showed in a series of 86 patients with prostate cancer metastases that metastases involving the axial skeleton carry a better prognosis than lesions in appendicular sites. It has also been demonstrated that percentage of positive area for metastases on a bone scan independently predicts survival in metastatic prostate cancer [20] .…”
Section: Discussionmentioning
confidence: 99%
“…Oefelein et al [12] reported that skeletal fractures are correlated with decreased overall survival in patients receiving long-term ADT for prostate cancer. Moreover, Noguchi et al [14] found a significant inverse correlation between the percentage of the skeleton affected by metastatic prostate cancer (detected by bone scintigraphy) and survival in a large-scale retrospective analysis. Bone metastases can perturb bone metabolism, as indicated by changes in biochemical markers of bone metabolism (osteolysis and osteogenesis) [15].…”
Section: Importance Of Skeletal Health and Rationale For Bisphosphonamentioning
confidence: 97%
“…Other proposals include an automated assessment of the percentage of involvement by metastatic bone disease on bone scintigraphy to monitor response to therapy. Although scoring systems of this type may relate to prognosis and response to therapy, they can be time consuming and variable (Sabbatini et al, 1999;Noguchi et al, 2003). Other limiting factors are the lack of anatomical detail.…”
Section: Bone Scintigraphy In Assessment Of Bone Metastasesmentioning
confidence: 99%